Assessing the plurilingual competence and plurilingual individuals’ skills and knowledge: similarities and divergences - Melo-Pfeifer, Sílvia; Ollivier, Christian (Frontiers in Communication, 2025)
IntroductionThis paper defines plurilingual assessment and shows the semantic ambiguities present in the concept. Specifically, it addresses two understandings of the concept: one related to the valuation of the plurilingual individual and the other to the evaluation of the plurilingual competence.MethodsThe above-mentioned distinction is treated theoretically only, through the revision of available and emergent literature, which serve as a springboard to present, describe, and compare two European projects dealing with plurilingual assessment in formal language education settings.ResultsThe two European projects present commonalities and differences and show that the valuation of the plurilingual individual and the evaluation of the plurilingual competence can be blurred in assessment practices.DiscussionThe paper finishes with recommendations for the development of plurilingual pedagogical and assessment approaches for all students, as a way to enhance the plurilingual competence of all at school.